1999
DOI: 10.1046/j.1365-2796.1999.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of LDL apheresis on carotid arterial atherosclerosis in familial hypercholesterolaemic patients

Abstract: Abstract. Koga N, Kurashige Y, Sato T (Koga Hospital, Kurume, Japan). Long-term effects of LDL apheresis on carotid arterial atherosclerosis in familial hypercholesterolaemic patients. J Intern Med 246: 35]43.Objectives. To assess the long-term effect of LDL apheresis on carotid arterial atherosclerosis in severe familial hypercholesterolaemic (FH) patients. Design. Changes in existing plaque, new plaque formation and annual progression rate of carotid early plaque were evaluated by B-mode ultrasonography. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 24 publications
2
15
0
3
Order By: Relevance
“…Cerebral disease plays a minor role in the morbidity in HFH reported in the literature and as shown above, despite the severe carotid stenosis in our patients, none had cerebral symptoms. Whether this means different clinical manifestations between the coronary and cerebral circulation exist, implicating that a less invasive approach toward cerebral atherosclerosis is warranted requires further investigation as LDL apheresis has shown to retard progression of intima-medial thickness [14].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral disease plays a minor role in the morbidity in HFH reported in the literature and as shown above, despite the severe carotid stenosis in our patients, none had cerebral symptoms. Whether this means different clinical manifestations between the coronary and cerebral circulation exist, implicating that a less invasive approach toward cerebral atherosclerosis is warranted requires further investigation as LDL apheresis has shown to retard progression of intima-medial thickness [14].…”
Section: Discussionmentioning
confidence: 99%
“…In 1999, Koga et al [136] published a study examining the long-term effect of LA on carotid artery atherosclerosis. Eleven FH patients received LA for an average of 7.8 years, while 10 control FH patients received medication only for an average of 5.5 years.…”
Section: Effect Of La On Carotid Artery Stenosis and Peripheral Artermentioning
confidence: 99%
“…In a study of seven patients with heterozygous FH, HELP apheresis reduced total and LDL cholesterol and fi brinogen levels, and led to a signifi cant reduction in carotid plaque volume [29]. An additional study suggesting a benefi t from LDL apheresis demonstrated carotid plaque regression compared with the control group in two patients with homozygous FH and nine with heterozygous FH [30]. The benefi t of LDL apheresis also was demonstrated in a study of peripheral arterial disease examining the effects of LDL apheresis on aortotibial stenosis and carotid intima-media thickness.…”
Section: Carotid and Peripheral Arterial Diseasementioning
confidence: 99%